A HUMAN CAPACITY APPROACH IN FAMILY BUSINESS FOR POVERTY REDUCTION (Marketing Journal, 2025)
This article provides a scientific -theoretical analysis of the role of family entrepreneurship in the process of reducing poverty levels and its significance within the framework of the concept of expanding human capabilities. The study examines the positi on of family entrepreneurship in the national economy, its impact on socio - economic development, and its influence on poverty reduction. Additionally, a system of factors aimed at increasing the efficiency of family entrepreneurship is developed, and the i mpact of these factors on economic stability is substantiated from a scientific perspective. The article evaluates the effectiveness of strategies for the development of 66 family entrepreneurship and poverty reduction, while also presenting practical and theoretical recommendations for their further improvement.
Keywords: globalization; poverty level; family enterprises; family business; family entrepreneurship; small business; action strategy; vulnerable population